Pemanfaatan dataset ukuran efek (effect size) untuk membangun alternatif model penelitian: Studi kasus minat konsumen membeli kendaraan listrik - Putri, Rizkiya Anisyah; Yoganingrum, Ambar; Febriandirza, Arafat; Asmara, Indri Juwita; Rezaldi, Muhammad Yudhi; Tohari, Amin; Prasetyadi, Abdurrakhman; Indrawati, Ariani; Siagian, Al Hafiz Akbar Maulana (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2024)
This study presents survey data from primary research papers containing effect size data and the number of respondents for several variables influencing consumer interest in purchasing electric vehicles. The survey utilized the Meta-Analytic Structural Equation Modeling (MASEM) approach. Data were collected in June 2021 using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to identify 11 valid papers. This survey aimed to collect effect size values, such as path coefficients and standardized regression weights, from each of the eleven papers. The effect size values collected indicate the magnitude of the relationship between the variables: Attitude, Perceived Behavior Control, Subject Norm, Charging Infrastructure, Environmental Concern, Financial Benefit, External Environment, Marketing Mix, Willingness to Pay a Premium, Incentive Policy Measures, and Perceived Value, and their impact on interest in purchasing electric vehicles. The data set stored in this repository can serve as a reference for researchers and policymakers in developing models and examining the relationship between variables influencing electric vehicles adoption.